Reinforcement and deformation behaviors of polyvinyl alcohol/graphene/montmorillonite clay composites. (30th October 2015) - Li, Chengpeng; Li, Yongzhen; She, Xiaodong; Vongsvivut, Jitraporn; Li, Jihua; She, Fenghua; Gao, Weimin; Kong, Lingxue
Abstract: We report the synergistic reinforcement and deformation of polyvinyl alcohol (PVA)/graphene/montmorillonite clay (MMT) composites with the tensile properties being improved greatly. Particularly, the tensile strength and modulus of PVA composite with 0.9 wt% graphene and 0.3 wt% of MMT were improved by more than 58% and 43% when compared to the neat PVA, respectively, and were at least 10% higher than the enhanced sum of dual PVA composites with 0.9 wt% graphene and 0.3 wt% MMT. This reinforcement was resulted from the good dispersion and effective interfacial interactions as confirmed from morphology investigation, increased glass transition temperature and the shift of O–H stretching. When there were no fillers i.e. in situ reduced graphene (IRG) or MMT or their loading was low, high alignment of PVA could be observed, with increased crystallinity, melting point, lamellae thickness but narrowed crystallite size distribution. The synergistic reinforcement of PVA achieved from combined incorporation of IRG and MMT will pave the way for the development of stronger PVA composites in various applications. Graphical abstract: